2014 9th International Conference on Industrial and Information Systems (ICIIS) 2014
DOI: 10.1109/iciinfs.2014.7036582
|View full text |Cite
|
Sign up to set email alerts
|

On reduction of oscillations in target tracking by artificial potential field method

Abstract: Artificial potential field is a powerful method of navigation for mobile robots in a cluttered environment. Despite the advantages that it offers, this method is not free from local minima and oscillation problems. This paper addresses the oscillation problem near the obstacles and in narrow passages. A comparative study has been made between the traditional gradient descent technique and second order methods and it has been shown that the Levenberg-Marquardt algorithm improves upon the oscillation problem and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…12 a ). Biswas and Kar [31] state that swings in the trajectories associated with APF have not yet been wholly cancelled out, especially in narrow passages between a cluster of obstacles. Additionally, the vehicles with APF slightly oscillate around their goal.…”
Section: Computer Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 a ). Biswas and Kar [31] state that swings in the trajectories associated with APF have not yet been wholly cancelled out, especially in narrow passages between a cluster of obstacles. Additionally, the vehicles with APF slightly oscillate around their goal.…”
Section: Computer Simulationsmentioning
confidence: 99%
“…A potential field method was used in [16, 30] to achieve inter‐unmanned aerial vehicle (UAV) collision avoidance using a virtual repulsive force derived from the negative gradient of a potential function. The force calculating method may cause oscillations in the trajectory or even getting stuck due to local minima [31]. These observations have inspired us to conduct the research work presented in this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are potential cases that the robot moves across the complex potential field area at a big pace of movement and positioning errors occur due to poor radio propagation. Relevant researchers have shown that when high motion speed and GPS positioning errors are taken into account, the trajectory of the robot is likely to shake violently [15][16]. As shown in Figure 1, when the robot moves between obstacles or in the aisle, the sharp change of direction problem is extremely serious.…”
Section: B Path Planning For Mobile Robotsmentioning
confidence: 99%
“…In work of [16] the traditional gradient descent technique is compared with the second-order optimization method, and its results show that the Levenberg-Marquardt algorithm can improve the jitter problem and generate smoother trajectory with fewer steps.…”
Section: B Path Planning For Mobile Robotsmentioning
confidence: 99%